2022
DOI: 10.1038/s41467-022-28822-7
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin-1 sensitive lysine-136 acetylation drives phase separation and pathological aggregation of TDP-43

Abstract: Trans-activation response DNA-binding protein of 43  kDa (TDP-43) regulates RNA processing and forms neuropathological aggregates in patients with amyotrophic lateral sclerosis and frontotemporal lobar degeneration. Investigating TDP-43 post-translational modifications, we discovered that K84 acetylation reduced nuclear import whereas K136 acetylation impaired RNA binding and splicing capabilities of TDP-43. Such failure of RNA interaction triggered TDP-43 phase separation mediated by the C-terminal low comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…Acetylation of K82, at position P 1 ′ ( Figure 7C ), and ubiquitination of the nearby K79 (at position P −1 ′) were found in a sarkosyl-insoluble fraction of TDP-43 aggregates isolated from brains of ALS patients ( Kametani et al, 2016 ). Acetylation of K84 at the P 3 ′ position ( Garcia Morato et al, 2022 ) resulted in TDP-43 cytoplasmic mislocalization, and aggregation propensity in HEK293E cells, strengthening the connection between modification of the TDP-43 minor NLS box and pathogenicity. Similarly, as previously pointed out, K84A and K84R mutations largely prevented the nuclear import of an RFP-TDP-43-NLS reporter, indicating K84 is crucial for the function of the TDP-43 NLS ( Khosravi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 89%
“…Acetylation of K82, at position P 1 ′ ( Figure 7C ), and ubiquitination of the nearby K79 (at position P −1 ′) were found in a sarkosyl-insoluble fraction of TDP-43 aggregates isolated from brains of ALS patients ( Kametani et al, 2016 ). Acetylation of K84 at the P 3 ′ position ( Garcia Morato et al, 2022 ) resulted in TDP-43 cytoplasmic mislocalization, and aggregation propensity in HEK293E cells, strengthening the connection between modification of the TDP-43 minor NLS box and pathogenicity. Similarly, as previously pointed out, K84A and K84R mutations largely prevented the nuclear import of an RFP-TDP-43-NLS reporter, indicating K84 is crucial for the function of the TDP-43 NLS ( Khosravi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 89%
“…ubiquitination, methylation, acetylation and SUMOylation) that can impact physiological function and cellular processes (Wang and Cole, 2020). For instance, TDP-43's lysine 136 is prone to acetylation and Garcia Morato et al showed that acetyl-mimic K136Q reduces RNA binding and that both acetyl-mimic and acetyl-dead K136R disrupts exon 9 CFTR splicing activity, implicating RNA interactions in LLPS (Garcia Morato et al, 2022). Further analysis of K136Q condensates revealed reduced motility, size and fusion events compared to TDP-43 WT .…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, these effects of aberrant phase separation were limited to the mutation of the single lysine 136 while the disease-linked mutation (G294V) had no effect on these LLPS characteristics. Garcia and colleagues reported in their in vitro study that the acetylation-mimic variant K136Q (instead of acetylation- and SUMO-deficient K136R) showed a slower FRAP recovery and formation of larger aggregates in vitro (Garcia Morato et al, 2022). These findings are aligned with our in vivo LLPS observations of the K136R variant showing the opposite effects.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Garcia Morato et al found that Lys79 and Lys84 could be acetylated in a non-neuronal cell model. [53] Addition of this modification to Lys84 increased the cytoplasmic concentration of full-length TDP-43. [53] Lys84 occupies the P 3 ' position immediately downstream of the P 2 ' position.…”
Section: Post-translational Modificationsmentioning
confidence: 99%